Estádio fenológico e nitrogênio como fatores de variação na composição química e atividade alelopática de capim-annoni - Cecchin, Kalinca (2015)
The aim of this study was to verify if the nitrogen fertilization and the phonological stage affect the chemicalbromatological composition and the allelopathic action of tough lovegrass (Eragrostis plana Nees). The treatments consisted of the combination of nitrogen levels (0,100 and 200 kg.ha-1 N) and phenological stages during harvest (vegetative and flowering). It was verified as for: 1) Growth and biomass allocation: increase plant height in response to the increase N levels and maturity in the plants, as well as increase leaves partition in flowering stage with application of extreme levels of N and increase in the culm partition with the N intermediate levels; 2) Bromatologic composition evaluated by near infrared spectroscopy method: increase in crude protein content in response to the increase in the N levels and plants harvested in the flowering stage; for neutral detergent fiber and hemicellulose, was effect of phenological stage, with higher values in plants harvested in the vegetative stage. 3) Chemical composition evaluated by high performance liquid chromatography: the extracts showed the acids caffeic, ferulic, vanillic and p-coumaric; the monomeric procyanidins epicatechin and catechin; and the coumarin (1,2 benzopyran). The phenolic acids had a higher concentration in plants in the flowering plant and with levels of 0 and 200 kg.ha-1 N. The concentration of catechin, in plants in the vegetative stage, had higher in levels of 0 e 100 kg.ha-1 N, not allowing that this nutrient affected their content in the flowering. The quantity of epicatechin showed opposite behavior, with increased of the concentration higher N levels in vegetative stage and higher concentration in the absence of N in flowered plants. The concentration of coumarin was not affected by the phenological stage, but has its low concentration in the intermediate N levels. 4) Allelopathic activity of tough lovegrass aqueous extracts in lettuce seeds (Lactuca sativa L.): was verified that material coming from plants harvested in the vegetative stage and treated with the N intermediate levels were more heterotoxic. Therefore, the growth stage and nitrogen fertilization are interactive factors affecting the chemical-bromatological composition and the allelopathic activity of tough lovegras